Improving Digital Literacy Skills for Mekarbuana Village Officials - Nono Heryana; Rini Mayasari; Agung Susilo Yuda Irawan; Bagja Nugraha (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The village is the smallest part of the public service provider that is in direct contact with the community as the recipient of public services. The digital literacy ability of village officials is the most important aspect in supporting optimal services to the community. UNESCO defines digital literacy as the ability to use information and communication technologies. The purpose of this activity is that the application of digital literacy will make the socio-cultural life of the community tend to be safe and conducive. Building a digital literacy culture also needs to involve the active role of the entire community, especially the Mekarbuana village apparatus. Based on the results of the pre-test and post-test evaluations, Mekarbuana village officials were able to understand digital literacy well and knew that the training materials provided could be useful in improving public services in Mekarbuana village.